Age-related changes in the colonic blood supply: their relevance to ischaemic colitis. Issue 5 (May 1978) - Binns, J C; Isaacson, P
Abstract : Ischaemic colitis due to non-occlusive mesenteric ischaemia is a disease of the elderly which commonly involves the left side of the colon; selective splenic flexure involvement is said to be especially common. In an attempt to explain these features postmortem angiograms were performed on the superior and inferior mesenteric arteries of 37 postmortem subjects. A distinct age-related tortuosity of the long colic arteries was noted which could account for the increasing incidence of ischaemic colitis with age. No anatomical basis for the higher incidence of left-sided involvement was found and, specifically, no critical point in the arterial circulation at the splenic flexure was demonstrated.